Renal Cell Carcinoma with Direct Extension into the Gonadal Vein, Uterus, Fallopian Tube, and Bilateral Ovaries: A Case Report (Journal of Kidney Cancer, 2020)
Renal cell carcinoma (RCC) with invasion into the renal vein is well described; however, invasion into the gonadal vein is a rare event with less than five cases reported in the literature. RCC occasionally presents with metastasis to the ovaries or the fallopian tubes, although this is also a rare occurrence. We present a case of locally advanced left RCC with direct extension into the ipsilateral gonadal vein with extension into the bilateral ovaries and uterus, which has not been previously described. Computed tomography (CT) in a 72-year-old female with a 35-pound weight loss indicated the presence of a 16-cm left renal mass with caudal tumor extension through the left gonadal vein and regional lymph-adenopathy. There was no evidence of distant metastasis, and she underwent an open left radical nephrectomy. Intraoperatively, she was found to have direct extension of the tumor through the left gonadal vein into the uterus, bilateral ovaries, and the left fallopian tube. All visible dis-ease was resected, and retroperitoneal and pelvic lymphadenectomy were performed. The patient had an uneventful hospital course. Pathology revealed clear cell RCC, Fuhrman grade 3. The final pathologic stage was pT4N1M1. The patient was ultimately noted to have pulmonary metastasis and was treated with immunotherapy with no evidence of disease progression.